Evaluation of the color stability of two techniques for reproducing artificial irides after microwave polymerization - Goiato, Marcelo Coelho [UNESP]; dos Santos, Daniela Micheline [UNESP]; Moreno, Amália [UNESP]; Gennari-Filho, Humberto [UNESP]; Pellizzer, Eduardo Piza [UNESP] (FapUNIFESP (SciELO), 2011)
The use of ocular prostheses for ophthalmic patients aims to rebuild facial aesthetics and provide an artificial substitute to the visual organ. Natural intemperate conditions promote discoloration of artificial irides and many studies have attempted to produce irides with greater chromatic paint durability using different paint materials. Objectives: The present study evaluated the color stability of artificial irides obtained with two techniques (oil painting and digital image) and submitted to microwave polymerization. Material and Methods: Forty samples were fabricated simulating ocular prostheses. Each sample was constituted by one disc of acrylic resin N1 and one disc of colorless acrylic resin with the iris interposed between the discs. The irides in brown and blue color were obtained by oil painting or digital image. The color stability was determined by a reflection spectrophotometer and measurements were taken before and after microwave polymerization. Statistical analysis of the techniques for reproducing artificial irides was performed by applying the normal data distribution test followed by 2-way ANOVA and Tukey HSD test (α=.05). Results: Chromatic alterations occurred in all specimens and statistically significant differences were observed between the oil-painted samples and those obtained by digital imaging. There was no statistical difference between the brown and blue colors. Independently of technique, all samples suffered color alterations after microwave polymerization. Conclusion: The digital imaging technique for reproducing irides presented better color stability after microwave polymerization.
Keywords: Artificial eye; Color; Paint